Psychometric Properties of the Chinese Irrational Procrastination Scale: Factor Structure and Measurement Invariance Across Gender - Shaw, Amy; Zhang, Jennifer J. (Frontiers in Psychology, 2021)
The present paper reports on the preliminary validation of a Chinese version of the Irrational Procrastination Scale (IPS; Steel, 2002, 2010). To this end, the 9 items of the IPS were translated into Chinese and data were collected from a sample of 2,361 mainland Chinese college students. Confirmatory factor analysis (CFA) was used to examine the dimensional structure of the IPS and multigroup CFA (MG CFA) was carried out to evaluate the measurement invariance across gender. Results revealed that the Chinese IPS had adequate internal consistency reliability, adhered to the one-factor structure, and exhibited strong or scalar invariance across the two gender subgroups, thereby providing support for the internal construct validity of the scale. Additionally, the IPS scores were found to be strongly and negatively related to the Conscientiousness personality trait while showing weak correlations with the other traits, which provided some support for the convergent and divergent validity of the Chinese IPS. Study limitations and future research directions (e.g., expanding the empirical evidence for the scale’s external validity) are discussed.